Translucency and contrast ratio of dimethacrylate resin based dental materials after bleaching: an in-vitro study - Nilgun Akgul; Merve Nur Yilmaz (BMC Oral Health)
Abstract Objective To compare the translucency and contrast ratio of 13 different resin based restorative materials and to evaluate the effect of 2 different bleaching methods on the translucency and contrast ratio of these materials. Methods In this study, a total of 260 samples were prepared, 20 from each of 13 different dimethacrylate-based restorative materials. Then, each material group was divided into 4 subgroups. While two different bleaching methods (home and office) were applied to two of these groups, the other two groups were created as separate control groups for each bleaching group. After the bleaching process, Translucency Parameters (TP) and Contrast Ratio (CR) were calculated with a spectrophotometer. The data obtained were analyzed using two-way ANOVA and Tukey post-hoc tests (p < 0.05). Results When the bleaching groups were compared in terms of the differences between the TP values ​​in general, it was seen that the TP values ​​decreased in all groups, but this decrease was least in Opalescence PF. In terms of materials, the greatest change in TP and CR values ​​was seen in composite materials, while the least change was seen in hybrid CAD/CAM materials. Conclusions Within the limitations of this in vitro study, the effect of bleaching agents on the translucency and contrast ratio of restorative materials depends on the material used and the bleaching method applied. Composite-based materials have been found to be more risky in terms of bleaching. For this reason, the clinician should take this into consideration, especially when performing office bleaching on teeth with restorations.